2006
DOI: 10.1177/0886260506294239
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Physical Assault and Rape Among Six Native American Tribes

Abstract: Prevalence and correlates of adult physical assault and rape in six Native American tribes are presented (N = 1,368). Among women, 45% reported being physically assaulted and 14% were raped since age 18 years. For men, figures were 36% and 2%, respectively. Demographic characteristics, adverse childhood experiences, adulthood alcohol dependence, and cultural and regional variables were assessed. Using logistic regression, predictors of physical assault among women were marital status, an alcoholic parent, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 43 publications
4
65
0
Order By: Relevance
“…Indeed, it is possible that differences within any given racial classification are larger than differences between racial groups. In fact, significant differences in the likelihood of SA have been documented across subgroups of Native Americans (Yuan, Koss, Polacca, & Goldman, 2006). Future studies of SA might benefit from further exploring the dynamics of cultural and ethnic differences that exist within racial groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is possible that differences within any given racial classification are larger than differences between racial groups. In fact, significant differences in the likelihood of SA have been documented across subgroups of Native Americans (Yuan, Koss, Polacca, & Goldman, 2006). Future studies of SA might benefit from further exploring the dynamics of cultural and ethnic differences that exist within racial groups.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, very few studies examine correlates of IPV in Asian populations (Chang et al, 2009;Leung & Cheung, 2008;Siewert & Flanagan, 2000;Yick, 2000;Yick, Shibusawa, & Agbayani-Siewert, 2000) and even fewer examine Native American populations (Harwell, Moore, & Spence, 2003;Yuan, Koss, Polacca, & Goldman, 2006). Yick and Agbayani-Siewert (2000) determined that those Asian couples that justified violence for particular situations were more likely to be victims or perpetrators of previous violence, and Chang et al (2009) found that immigrant respondents were less likely to report IPV than U.S. born Asian respondents.…”
Section: Risk Factors and Developing Culturally Focused Approaches Bymentioning
confidence: 99%
“…While no association was observed with the conjugal or social situation of indigenous women, divorce or separation from a partner, as well as unemployment was associated with a previous history of sexual abuse in non-indigenous women. Yuan, Koss, Polacca, and Goldman (2006) studied physical assault and rape in adults from six U.S. Native tribes.…”
Section: Introductionmentioning
confidence: 99%